Barriers to physical activity among adults in primary healthcare units in the National Health System: a cross-sectional study in Brazil - Souza, Ana Luísa Kuehn de; Santos, Letícia Pechnicki dos; Rech, Cassiano Ricardo; Rodriguez-Añez, Ciro Romelio; Alberico, Claudia; Borges, Lucélia Justino; Fermino, Rogério César (São Paulo Medical Journal, 2022)
BACKGROUND: Many factors may negatively impact physical activity (PA), but studies lack evidence of individual predictors of perceived barriers to PA among adults in primary healthcare units. OBJECTIVE: To analyze associations between sociodemographic characteristics, health conditions, leisure-time physical activity (LTPA), PA counseling and perceived barriers to LTPA among adult patients in primary healthcare units of the National Health System in Brazil. DESIGN AND SETTING: Cross-sectional study on a representative sample of adults in primary healthcare units in São José dos Pinhais, Paraná, Brazil. METHODS: This study was conducted in 2019, among 779 adults (70% women). Barriers to LTPA, socio-demographic characteristics (sex, age, marital status, skin color, education and income), health conditions (body mass index, hypertension, diabetes, dyslipidemia, coronary disease and medications), LTPA level and PA counseling received were measured using validated, standardized procedures. The data were analyzed using chi-square and Mann-Whitney U tests. RESULTS: The most prevalent barriers were “feeling too tired” (53%) and “lack of time” (52%). PA counseling was inversely associated with “lack of time” (45% versus 57%; P < 0.001) but positively associated with “injury or disease” (38% versus 29%; P = 0.008). There was an inverse linear trend between the number of barriers and LTPA (walking and total) (P < 0.001). Most barriers differed in comparisons of sociodemographic characteristics, health conditions, LTPA and counseling (P < 0.05). CONCLUSIONS: The barriers vary according to the individual predictors. Counseling strategies need to be specific for each barrier and may be promising for promoting LTPA within primary healthcare.